Estimation of the wideband interference nulling capability of a linear equi-spaced antenna array having a tapped delay line beamformer - Materum, Lawrence Y. 1978- (2003)
One measure of how well a particular adaptive antenna array configuration performs is its capability to reject interference signals in order to meet a certain performance goal. When the interference signals are wideband, the determination of the nulling capability of the antenna array is not as straightforward. In this research we attempt to quantify the maximum number of wideband interference signals that can be sufficiently nulled, under severe interference scenarios using a tapped delay line beamformer with a fixed number of antenna elements. This objective was accomplished through computer simulations where the performance of the tapped delay line beamformer is evaluated under various parameter settings and subjected to various interference scenarios. It is shown that increasing fractional bandwidth more taps are needed but to a certain limit. Also the results show that under severe interference scenarios, the maximum number of wideband interference signals than an array can sufficiently null with the minimal number of taps cannot improve beyond M-2.